From working in the wheat field to managing wheat: Women innovators in Nepal - Farnworth, Cathy Rozel; Jafry, Tahseen; Lama, Kanchan; Chatterjee, Sushila; Badstue, Lone B. (Springer, 2019)
This article presents research conducted in Nepal’s Terai plains in 2014-15 showing that women are innovating in wheat to the extent that wheat farming is experiencing a shift from feminization of agricultural labor towards women taking control over decision making. Processes accounting for this include male out-migration, non-governmental organizations working on promoting women’s equality that has developed women’s confidence, individual support from extension agents, and strong cooperation between women to foster each other’s “innovation journeys.”